Effect of a Bacillus velezensis and Lysinibacillus fusiformis-based biofertilizer on phosphorus acquisition and grain yield of soybean - Vitorino, Luciana Cristina; da Silva, Elias José; Oliveira, Marilene Silva; Silva, Isabella de Oliveira; Santos, Lorraine da Silva; Mendonça, Maria Andréia Corrêa; Oliveira, Thais Cristina Sousa; Bessa, Layara Alexandre (Frontiers in Plant Science, 2024)
Introduction Phosphate-solubilizing bacteria that function through acidification (organic acid synthesis) or mineralization (production of enzymes such as phytase and phosphatases) have been explored as a biotechnological alternative to enhance plant access to phosphorus (P) retained in organic and inorganic forms in agricultural soils. This study tested the hypothesis that applying a biofertilizer composed of a recognized phosphate-solubilizing bacterium (Bacillus velezensis – endophytic strain BVPS01) and an underexplored plant growth-promoting bacterium (Lysinibacillus fusiformis – endophytic strain BVPS02) would improve the growth and grain yield of Glycine max L. plants. Methods Initial in vitro tests assessed the functional traits of these bacteria, and a mix of strains BVPS01 and BVPS02 was produced and tested under field conditions to evaluate its agronomic efficiency. Results The results confirmed the hypothesis that the tested biofertilizer enhances the agronomic performance of G. max plants in the field. The B. velezensis strain (BVPS01) was found to be more effective than the L. fusiformis strain (BVPS02) in solubilizing phosphates via the phosphatase enzyme production pathway, indicated by the expression of the phoC and phoD genes. In contrast, L. fusiformis was more effective in solubilizing phosphates through organic acid and phytase-related pathways, in addition to synthesizing indole-3-acetic acid and increasing the mitotic index in the root meristem of G. max plants. These strains exhibited biological compatibility, and the formulated product based on these rhizobacteria enhanced root development and increased the number of nodules and flowers, positively affecting 1000-grain weight, grain yield, and grain P content. Discussion Thus, the tested biofertilizer demonstrated potential to improve root growth and increase both the yield and quality of soybean crops, making it a sustainable and low-cost strategy.